Відвернення світової війни та боротьба з міжнародним тероризмом - Андрущенко, Т. В.; Андрущенко, Т. В.; Andrushhenko, T. (My University, 2012)
The problems of prevention of world war threat which is created by modern international terrorism are examined in the article. Experience and degree of effi ciency of antiterroristic actions are analysed.
Андрущенко Т. В. Відвернення світової війни та боротьба з міжнародним тероризмом /Т. В. Андрущенко // Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 46. – С. 109-118.
Keywords: міжнародний тероризм; загроза новой світової війни; запобігання загрозі нової світової війни; досвід та ступінь ефективності антитерористичних дій; международный терроризм; угроза новой мировой войны; предотвращение угрозы новой мировой войны; опыт и степень эффективности антитеррористических действий; international terrorism; the threat of a new world war; preventing the threat of a new world war; experience and the degree of effectiveness of anti-terrorist action